MicroRNAs expressed during normal wound healing and their associated pathways: A systematic review and bioinformatics analysis - Morgana Lüdtke Azevedo; Roberta Giorgi Silveira; Fernanda Nedel; Rafael Guerra Lund (PLoS ONE, 2023)
MicroRNAs (miRNAs) are responsible for regulating gene expression post-transcriptionally. Are involved in several biological processes, such as wound healing. Understanding the miRNAs involved in this process is fundamental for the development of new therapies. So, due to the need to understand the role of these molecules, we aimed systematically review the literature in order to identify which miRNAs are involved in the wound healing and determine, through bioinformatics analysis, which signaling pathways are associated with these miRNAs. An electronic search was performed in the following databases: National Library of Medicine National Institutes of Health (PubMed), Science Direct, Scifinder, Scopus and Web of Science, using the descriptors: “(microRNA [MeSH])” and “(skin [MeSH])” and “(wound healing [MeSH])”. After the search, two independent and previously calibrated reviewers selected the articles that analyzed the expression pattern of miRNAs in wound healing in in vivo studies, using the software Zotero bibliography manager. Following, bioinformatic analysis was performed using the software DIANA Tools, mirPath v.3 and the data was interpreted. The bioinformatics analysis revealed that on the day 1 there were 13 union pathways, eight of which were statistically significant. Still on the day 1, among the miRNAs that had a decrease in their expression, 12 of 17 union pathways found were statistically significant. On the day 5, among the miRNAs with an increase in expression, 16 union pathways were found, 12 of which were statistically significant. Finally, among the miRNAs with decreased expression, 11 of 15 union pathways found were statistically significant. Although it has been found substantial heterogeneity in the studies, with this systematic review, it was possible to study the panorama of miRNAs that may be altered in the wound healing. The present review summarizes existing evidence of miRNAs associated to wound healing, and these findings can contribute to new therapeutic approaches.